Visualizing Variability in Ceramic Micro-Curvature though Novel 3D Morphometric Mapping and Sliced Segmental Extraction - James Frances Loftus III; Noriko Seguchi (Journal of Computer Applications in Archaeology, 2022)
In recent years, two-dimensional (2D) outline-based morphometric analysis has begun to be the standard means of shape analysis in the study of ceramics. Despite the ever-increasing repertoire of three-dimensional (3D) ceramic data available to researchers, due to challenges in utilizing landmark-based geometric morphometrics on ceramics, many contemporary studies are forced to rely on 2D outlines, which account for only a small degree of shape variance. Consequently, notions of intra-vessel variance cannot be thoroughly extrapolated, and as such, important themes such as morphogenesis during the production process have not been thoroughly examined. By contrast, the present project utilizes a method derived from high-resolution 3D scans combining “morphometric mapping” and “sliced segmental extraction” to visualize previously unrecognized variability in the micro-curvature of full vessels. This method does not require homologous landmarks, but rather, employs a multistage approach that allows for several stages of analysis that can be adjusted to each given research project, and thus has the potential to elucidate idiosyncratic variability during the morphogenesis process.   概要 近年、土器研究において、2次元の輪郭を用いた形状（形態）解析が主流となりつつある。土器の3次元データのレパートリーは増え続けているが、ランドマークを用い た幾何学的形態計測法を土器に適用することは困難であるため、多くの研究は形態のばらつきが小さい2次元外形図に頼らざるを得ない。そのため、製品内のばらつきの概念を十分に定義できず、製作過程における形態形成などの重要なテーマについては十分に検討されていない。これに対し、本研究では、高解像度3Dスキャンから得られる「形態計測マッピング法」と「セグメント抽出法」を組み合わせ、これまで認識されていなかった土器全体の表面の微小曲線のばらつきを可視化することに成功した。この手法は、相同ランドマークを必要とせず、研究プロジェクトごとに分析の様々な段階において調整可能な分析手法を採用しているため、形態形成過程における特異様式を明らかにできる可能性がある。   キーワード: 三次元分析; 土器; 日本考古 学; 形態計測マッピング法; セグメント抽出法